Assessment of Sustainable Tourism in Region 7 and Its Implication - Ralota, Eira Y.; Danojog, Mark Paul; Gurrea, Juan; Capucao, Roel P.; Casalta, Noreen Merryl L.; Tool Jr., Leonardo H.; Vasquez, , Mary Rose T.; Bergamo Jr., Remegio (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The tourism industry is one of the most forward-looking and dynamic in the world. It is critical to plan and grow tourism in a way that balances the needs of the environment, the economy, and society as a whole. Based on the findings it can be noted that the tourism industry cannot sustain itself without the help of community and local government units, which were mentioned in the interpretations of sustainable tourism by many local citizens and barangay officials. Hence, ensuring the sustainability of tourism development implies keeping high level of awareness and strong commitment among stakeholders regarding crucial issues like quality assurance and sustainable practices. The local government may support the development of tourism by allotting adequate budget that can be used for promotion and maintenance of the tourist destination. The participation of the local residents in the implementation of the tourism development plan may be solicited as with their local government.